PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PRODUK KECANTIKAN (STUDI KASUS PADA ROYAL JAVANA SPA LAHAT) - Darwin Kesuma, Heri Fitriadi, Intan Purnamasari (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2022)
Testing the effect of Product Quality (X1) on Customer Satisfaction (Y) with partial testing obtained t_count value for Product Quality variable (X1) obtained Sig value of 0,000 which means Sig 0,000 <0,05 which means the Product Quality variable (X1) has a significant effect on Customer Satisfaction (Y), then Ho is rejected and Ha is accepted, so the hypothesis in this study is shown to show a significant influence on Product Quality (X1) variable on Customer Satisfaction (Y). Testing the effect of Service Quality variable (X2) on Customer Satisfaction (Y) with partial testing obtained t_count value for Service Quality variable (X2) obtained Sig value of 0.339 which means Sig 0.339> 0.05, which means Service Quality variable (X2) is not significant effect on Customer Satisfaction (Y), then Ho is accepted and Ha is rejected, so the hypothesis in this study is not proven to show a significant influence on Service Quality (X2) variable on Customer Satisfaction (Y). The calculated F value is 39,367, with a significant level of 0.05, the Sig value is 0,000, which means Sig 0,000 <0,05, Ho is rejected and Ha is accepted. This means that the Product Quality variable (X1), and Service Quality (X2), influence together - the variable Customer Satisfaction (Y), so the hypothesis in this study proved to have a significant effect